Local knowledge about plants used in a high conservation value area of the Southern Yungas, Argentina - Acosta, Marina Eva; Politi, Natalia; Rivera, Luis Osvaldo (Ethnobotany Research and Applications, 2025)
Background: A study was conducted in the locality of El Fuerte (Santa Bárbara Department, Jujuy Province, Argentina). The objectives of this work were to (1) document the ethnospecies of plants used by local people, (2) understand their consensus for use and utilitarian versatility, (3) determine harvesting sites, and (4) assess the availability of plants used based on local perceptions. Methods: Open and semi-structured interviews were conducted to 11 collaborators, along with free listing, participant observation and species identification in the field. Results: A total of 124 ethnospecies were identified, of which 59% are native species, used for medicinal purposes (36%) and as food (33%). The most frequently mentioned botanical families across all species were Lamiaceae (19%), Rosaceae (16%), Fabaceae (14%), Asteraceae (12%), and Myrtaceae (9%). The species with the highest consensus for use were piquillín (Condalia cf. buxifolia) and mato (Myrcianthes pungens) and the most versatile of use were piquillín and molle (Schinus sp.). The plants were obtained from environments with both high (town) and low (forest) human intervention. Local people's perceptions of the availability of some plants indicate a decrease in terms of quantity. Conclusions: This is a first approach to study local ecological knowledge in the region, providing a general overview of the useful plants employed by its inhabitants. These findings aim to strengthen biocultural conservation of forests, promote sustainable resource management and offer economic alternatives for local people. Keywords: useful plants, ethnoconservation, native forest, Northwestern Argentina.